Partisipasi Kelompok Tani Hijau Lestari Dalam Kegiatan Penyuluhan Pertanian Di Desa Tondei Satu Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Bujung, Venrando Chandra Putra; Maweikere, Audrey Julia Maria; Baroleh, Jenny (Sam Ratulangi University, 2023)
This study aims to determine the participation of the Green Lestari farmer group in agricultural extension activities in Tondei Satu Village, West Motoling District, South Minahasa Regency. This research started from April to June 2022. The data analysis method used in this study was descriptive analysis using a Likert Scale, the number of samples used in this study totaled 11 people. The types of data used in this research are primary data and secondary data. Primary data was obtained from direct interviews with the Hijau Lestari farmer group using a questionnaire, while secondary data was obtained from the Tondei Satu Village Government. The results of this study indicate that the participation of the Hijau Lestari farmer group in agricultural extension activities in Tondei Satu Village, West Motoling District, South Minahasa Regency is classified as active. Where is the total overall score of 353 with a percentage of 89.14.